Conveying the Tragedy of War Through Unconventional Photography Methods - Ivashko, Yulia; Pawłowska, Aneta; Belinskyi, Serhii; Dmytrenko, Andrii (Faces of War, 2024)
This article analyses the specificity of conveying the tragedy of war through artistic photography. Comparing photos from the Vietnam War and the contemporary Russian-Ukrainian war illustrates how the range of figurative means has expanded. Photography of the Vietnam War had a narrow range of topics and limited methods of conveying content. In contrast, Ukrainian frontline photography is more diverse, with unconventional techniques emerging in military artistic photography. Many romantic photographs depicting landscapes and animals have surfaced, and the role of symbolism in photographic images has increased. This article aims to highlight the differences between past and present frontline photography while emphasising the greater symbolism and hidden meaning present in contemporary photography, as the tragedy of war resonates with the viewer through indirect allusions.